PELAKSANAAN PENGABDIAN MASYARAKAT DALAM MENINGKATKAN MOTIVASI BELAJAR MELALUI BIMBINGAN KLASIKAL DI SD NEGERI 105424 DESA BUKIT CERMIN - Alivia Fitri Salsabila; Aisyah Sekar Tri Wardani; Anisa Tulhalizah; Ida Farida; Ilham Kusuma Prabuningrat; Muhammad Atma Taher; Nur Hidayatil Janah; Putri Kiki Lestari (STKIP Subang, 2024)
This study aims to determine the level of learning motivation of students at SD Negeri 105424 Desa Bukit Cermin after the application of classical guidance. The research method used is a Qualitative research based on data in the field. The results of the research show that by implementing classical guidance to determine the learning motivation of grade 1 students at SD Negeri 105424 Bukit Cermin Village, through the implementation of community service, there is a difference between the level of student learning motivation before and after being given classical guidance services and classical guidance has an effect on increasing students' learning motivation. Based on this analysis, it can be concluded that the application of classical guidance to 1th grade students of SD Negeri 105424 Desa Bukit Cermin has an increase in learning motivation.